EFFECTIVENESS OF STUNTING PREVENTION PROGRAM AT BAJA HEALTH CENTER IN TANGERANG CITY - Suryani, Tri (Muhammadiyah International Public Health and Medicine Proceeding, 2023)
Stunting is a form of growth and developmental failure that causes linear growth disorders in toddlers due to the accumulation of nutritional deficiencies over a long period, starting from pregnancy to 24 months of age. The problem of malnutrition in Indonesia is a health issue that has not been fully addressed by the government. This can be seen from survey and research data such as the Basic Health Research (2018), which states that the prevalence of stunting (very short) in Indonesia is 19.3%, higher than in 2013 (19.2%) and 2007 (18%). Although many stunting prevention programs have been implemented by various parties and the health sector, these efforts have not effectively reduced the target number of stunting cases at the national level, posing a challenge for the health sector in preventing stunting cases. This research adopts a descriptive qualitative study design, where researchers aim to assess the effectiveness of the stunting prevention program in the working area of Baja Tangerang Health Center with three informants. Data collection techniques include interviewing related parties, observation, and documentation, with data analyzed by combining information from various existing sources. Health Center Baja has handled 2 children with malnutrition and 7 children with stunting. The results indicate that preventive measures must continue to be improved by meeting nutritional needs during pregnancy, monitoring child growth and development, and maintaining environmental hygiene. Integrated and multisectoral programs are needed to increase family income and prevent premature births (babies born not full term) to overcome the incidence of stunting in toddlers.